Duplicate US1 Genes of Duck Enteritis Virus Encode a Non-essential Immediate Early Protein Localized to the Nucleus - Li, Yangguang; Wu, Ying; Wang, Mingshu; Ma, YunChao; Jia, Renyong; Chen, Shun; Zhu, Dekang; Liu, Mafeng; Yang, Qiao; Zhao, Xinxin; Zhang, Shaqiu; Huang, Juan; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
The duplicate US1 genes of duck enteritis virus (DEV) encode a protein with a conserved Herpes_IE68 domain, which was found to be closely related to the herpes virus immediate early regulatory protein family and is highly conserved among counterparts encoded by Herpes_IE68 genes. Previous studies found the homologous proteins HSV-1 ICP22 and VZV ORF63/ORF70 to be critical for virus transcription and replication. However, little is known about the DEV ICP22 protein. In this paper, we describe the characteristics of this protein based on pharmacological experiments, real-time quantitative Polymerase Chain Reaction, Western blot, and immunofluorescence assays. We also investigate the role of the protein in DEV replication via mutation of US1. As a result, we found that the DEV ICP22 protein is a non-essential immediate early protein predominantly located in the nucleus of infected DEF cells and that DEV replication is impaired by US1 deletion. We also found that ICP22 contains a classical nuclear localization signal (NLS) at 305-312AA, and ICP22 cannot enter the nucleus by itself after mutating residue 309.